A method for preparing active material for lithium-sodium mixed ion battery

By using the preparation method of lithium-sodium mixed ion battery active materials in the preparation process of sodium iron phosphate and using nanometals as reducing agents, the carbon reduction steps are avoided, the problems of environmental pollution and low specific capacity are solved, and efficient Electrochemical properties and capacity retention.

CN116803898BActive Publication Date: 2025-02-18SICHUAN SIFUXUN ENERGY STORAGE TECH CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202310758621.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-06-26
Publication Date
2025-02-18
Estimated Expiration
2043-06-26

AI Technical Summary

Technical Problem

In the prior art, carbon reduction is prone to environmental pollution during the preparation of sodium ferric phosphate, and the prepared materials have a lower specific capacity, and the capacity attenuation is faster during the charging and discharging process.

Method used

Using the preparation method of lithium-sodium mixed ion battery active materials, using phosphorus source, iron source, sodium source and nanometal as reducing agents, Na1-zLizMxFeyPO4 materials were prepared through ball milling and sintering processes, avoiding the carbon reduction step and improving the Specific capacity and structural stability of the material.

Benefits of technology

The carbon-free reduction process is realized, which reduces environmental pollution, improves the specific capacity and electrochemical performance of sodium ferric phosphate, and extends the capacity retention rate during the charge and discharge process.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116803898B_ABST
    Figure CN116803898B_ABST
Patent Text Reader

Abstract

The invention discloses a method for preparing a lithium-sodium mixed ion battery active material, comprising: (1) using a phosphorus source, an iron source, and a sodium source as reaction raw materials, and using nano metals as a reducing agent, and mixing them in a set ratio to obtain a mixed product; (2) placing the mixed product under an inert atmosphere for ball milling, and placing the ball milled product under an inert atmosphere for primary sintering; (3) ball milling the primary sintered product and a lithium source, and then performing a secondary sintering on the ball milled product under an inert atmosphere, and grinding the product after cooling to obtain the lithium-sodium mixed ion battery active material; the chemical formula of the lithium-sodium mixed ion battery active material is Na 1‑z Li z M x Fe y PO4, 0<x<1, 0<y<1, 0<z≤0.2, M is selected from one or more of Mg, Al, Ti, V, Mn, Zn, and Cr. The present invention adopts a carbon-free reduction-secondary sintering process, which can effectively save energy and reduce emissions and reduce product costs; the secondary sintering process is used to solve the problem of inconsistent contract temperatures of lithium and sodium.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a method for preparing a lithium-sodium mixed ion battery active material, belonging to the technical field of sodium ion batteries. Background Art

[0002] Among the many positive electrode materials for sodium ion batteries, polyanionic compounds are considered to be the most promising type of electrode materials due to their excellent structural stability, safety and suitable voltage platform. Among them, sodium iron phosphate materials are abundant in raw materials, low in price, have three-dimensional ion diffusion channels, and good safety performance. Sodium iron phosphate NaFePO4 is given priority as a positive electrode material for sodium ion batteries. The theoretical specific capacity of olivine-structured NaFePO4 as a positive electrode material for sodium ion batteries is 154mAh / g.

[0003] CN 105161688A discloses a carbon-coated sodium iron phosphate-sodium vanadium phosphate composite material and a preparation method thereof. First, iron vanadate is prepared, and then the carbon-coated sodium iron phosphate-sodium vanadium phosphate is obtained by ball milling, re-milling, calcining and other steps using the iron vanadate as a raw material. The obtained material has a first charge and discharge capacity of 101.8 mAh·g at a voltage range of 2.0 to 4.0 V and a rate of 1C. -1 ; During the charge and discharge process, after 50 cycles at 1C, the capacity retention rate was 96.5%.

[0004] CN 115148976 A discloses a method for synthesizing sodium ferric phosphate pyrophosphate / carbon, a positive electrode material for a sodium ion battery, and a sodium ion battery thereof. The method comprises the following steps: adding deionized water to an organic phosphonic acid, an organic sodium acid, nano-ferric phosphate and a sodium source, stirring the mixture, heating and stirring the mixture to evaporate the mixture to dryness, drying the obtained solid, grinding the solid, pre-sintering the mixture under nitrogen protection, naturally cooling the solid, grinding the solid again, sintering the mixture under nitrogen protection, and naturally cooling the solid to obtain the sodium ferric phosphate pyrophosphate / carbon, a positive electrode material for a sodium ion battery.

[0005] The obtained material was charged and discharged at a rate of 1C in the voltage range of 2.0-4.2V. The material showed a typical charge-discharge curve of sodium iron pyrophosphate, and its first cycle discharge capacity was 99.38mAh g -1 , the capacity retention rate after 300 cycles is 94.2%.

[0006] In the prior art, the preparation process of sodium iron phosphate generally adopts carbon reduction for carbon coating or carbon doping to improve the conductivity of sodium iron phosphate. Carbon reduction is easy to cause environmental pollution, and the prepared sodium iron phosphate has a low specific capacity. During the charge and discharge process, due to the large radius of sodium ions, when the electrode material is embedded / de-embedded, it is easy to cause the electrode material to pulverize and collapse, thereby causing the charge and discharge capacity of the sodium battery to decay rapidly. Summary of the invention

[0007] In view of the shortcomings of the prior art, the purpose of the present invention is to provide a method for preparing active materials for lithium-sodium mixed ion batteries to solve the problems in the prior art that carbon reduction easily causes environmental pollution, the prepared sodium iron phosphate has a low specific capacity, and the capacity decays rapidly during charging and discharging.

[0008] In order to achieve the above object, the present invention provides the following technical solutions:

[0009] A method for preparing a lithium-sodium mixed ion battery active material comprises the following steps:

[0010] (1) using a phosphorus source, an iron source, and a sodium source as reaction raw materials and nano-metal as a reducing agent, mixing them in a set ratio to obtain a mixed product;

[0011] (2) ball milling the mixed product obtained in step (1) under an inert atmosphere, and sintering the ball milled product under an inert atmosphere to obtain a primary sintered product;

[0012] (3) ball-milling the primary sintered product obtained in step (2) and the lithium source, and then performing a secondary sintering on the ball-milled product under an inert atmosphere, and grinding the product after cooling to obtain;

[0013] The chemical formula of the active material of the lithium-sodium mixed ion battery is Na 1-z Li z M x Fe y PO4, 0<x<1, 0<y<1, 0<z≤0.2, M is selected from one or more of Mg, Al, Ti, V, Mn, Zn, Cr.

[0014] As a further improvement of the above technical solution, in step (1), the phosphorus source is one or more of diammonium dihydrogen phosphate, diammonium hydrogen phosphate, sodium dihydrogen phosphate and phosphorus pentoxide.

[0015] As a further improvement of the above technical solution, in step (1), the iron source is one or more of ferric phosphate and ferric oxide.

[0016] As a further improvement of the above technical solution, in step (1), the sodium source is one or more of sodium carbonate, sodium bicarbonate, sodium hydroxide, sodium acetate, sodium phosphate, sodium hydrogen phosphate, sodium oxalate, sodium formate, sodium citrate, sodium pyrophosphate and sodium metaphosphate.

[0017] As a further improvement of the above technical solution, in step (1), the lithium source is one or more of lithium carbonate, lithium hydroxide, lithium dihydrogen phosphate, dilithium hydrogen phosphate, and lithium phosphate.

[0018] As a further improvement of the above technical solution, in step (2), the mixed product is placed in a planetary ball mill for ball milling under an inert atmosphere, and the ball milling time is 0.5 to 24 hours.

[0019] The technical effect of the above improvement is that the ball milling process of the mixed product needs to be carried out under an inert atmosphere to prevent the nano-metal from being oxidized and affecting its reduction performance.

[0020] As a further improvement of the above technical solution, in step (2), the primary sintering temperature is 300-500° C., and the material insulation time is 4-12 hours.

[0021] As a further improvement of the above technical solution, in step (3), the primary sintering product and the lithium source are placed in a planetary ball mill for ball milling, and the ball milling time is 0.5 to 12 hours.

[0022] As a further improvement of the above technical solution, in step (3), the secondary sintering temperature is 600-800° C., and the material insulation time is 2-6 hours.

[0023] As a further improvement of the above technical solution, the inert atmosphere adopts any one of nitrogen, argon and helium.

[0024] The present invention also provides application of the preparation method of the lithium-sodium mixed ion battery active material in the preparation of sodium battery positive electrode materials.

[0025] The beneficial technical effects of the present invention are:

[0026] (1) The present invention provides a method for preparing active materials for lithium-sodium mixed ion batteries. According to the metal activity order of Mg, Al, Ti, Zr, V, Mn, Zn, Cr greater than Fe, nano-metal powders of Mg, Al, Ti, Zr, V, Mn, Zn, and Cr are selected as reducing agents to reduce high-valent iron. The raw materials are fully mixed using a ball mill in an inert atmosphere to improve the reaction activity.

[0027] (2) The present invention provides a method for preparing an active material for a lithium-sodium mixed ion battery. During the charge and discharge process, both lithium ions and sodium ions are deintercalated and deintercalated on the electrode. By using a portion of a lithium source to replace a sodium source, the utilization rate of lithium can be effectively improved. Since the radius of a lithium ion is smaller than that of a sodium ion, the structural stability of the electrode material during the charge and discharge process is improved.

[0028] (3) The present invention provides a method for preparing active materials for lithium-sodium mixed ion batteries, which adopts a carbon-free reduction-secondary sintering process. The carbon-free reduction process can effectively save energy and reduce emissions, and reduce product costs. The secondary sintering process is used to solve the problem of inconsistent contract temperatures of lithium and sodium. The NaM x Fe yPO4, secondary high temperature sintering and lithium source doping to obtain the lithium-sodium mixed ion battery active material Na 1-z Li z M x Fe y PO4.

[0029] (4) The lithium-sodium mixed ion battery active material prepared by the present invention exhibits excellent electrochemical performance. At room temperature, the capacity retention rate is 90.2% after 100 cycles at 1C, and the 0.1C discharge capacity reaches 121.7 mAh / g. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1 This is a SEM image of the active material of the lithium-sodium mixed ion battery in Example 1 of the present invention. DETAILED DESCRIPTION

[0031] The technical solutions in the embodiments of the present invention will be described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0032] Unless otherwise specified in this embodiment, the reagents used are all common commercial products or prepared by conventional means, and the equipment used are all conventional equipment in the art. The following are some embodiments of the inventor's experiments:

[0033] Example 1

[0034] A lithium-sodium mixed ion battery active material Na 0.9 Li 0.1 V 0.2 Fe 0.7 The preparation method of PO4 comprises the following steps:

[0035] (1) using diammonium dihydrogen phosphate, ferric oxide, and sodium carbonate as reaction raw materials and metallic vanadium powder as a reducing agent, and mixing them in a molar ratio of sodium, vanadium, iron, and phosphorus of 0.9:0.2:0.7:1 to obtain a mixed product;

[0036] (2) ball milling the mixed product obtained in step (1) under nitrogen for 6 hours, sintering the ball milled product under nitrogen at a temperature of 350° C. for 6 hours to obtain a primary sintered product;

[0037] (3) The primary sintered product obtained in step (2) and lithium hydroxide are ball-milled in a sodium to lithium molar ratio of 0.9:0.1, and the ball-milled product is secondary sintered under nitrogen at a secondary sintering temperature of 750° C. The material is kept warm for 4 hours. After cooling, the product is ground to obtain. Figure 1 This is a SEM image of the active material of the lithium-sodium mixed ion battery in Example 1.

[0038] Example 2

[0039] A lithium-sodium mixed ion battery active material Na 0.9 Li 0.1 Al 0.2 Fe 0.7 The preparation method of PO4 comprises the following steps:

[0040] (1) using sodium dihydrogen phosphate, iron phosphate, and sodium carbonate as reaction raw materials and metallic aluminum powder as a reducing agent, mixing them in a molar ratio of sodium, aluminum, iron, and phosphorus of 0.9:0.2:0.7:1 to obtain a mixed product;

[0041] (2) ball milling the mixed product obtained in step (1) under nitrogen for 6 hours, sintering the ball milled product under nitrogen at a temperature of 350° C. for 6 hours to obtain a primary sintered product;

[0042] (3) The primary sintered product obtained in step (2) and lithium hydroxide are ball-milled in a sodium to lithium molar ratio of 0.9:0.1, and the ball-milled product is secondary sintered under nitrogen at a secondary sintering temperature of 750° C. The material is kept warm for 4 hours. After cooling, the product is ground to obtain.

[0043] Example 3

[0044] A lithium-sodium mixed ion battery active material Na 0.8 Li 0.2 Mn 0.3 Fe 0.7 The preparation method of PO4 comprises the following steps:

[0045] (1) using sodium dihydrogen phosphate, iron phosphate, and sodium carbonate as reaction raw materials and metallic manganese powder as a reducing agent, mixing them in a molar ratio of sodium, manganese, iron, and phosphorus of 0.8:0.3:0.7:1 to obtain a mixed product;

[0046] (2) ball milling the mixed product obtained in step (1) under nitrogen for 6 hours, sintering the ball milled product under nitrogen at a temperature of 350° C. for 6 hours to obtain a primary sintered product;

[0047] (3) The primary sintered product obtained in step (2) and lithium hydroxide are ball-milled in a sodium to lithium molar ratio of 0.8:0.2, and the ball-milled product is secondary sintered under nitrogen at a secondary sintering temperature of 750° C. The material is kept warm for 4 hours. After cooling, the product is ground to obtain.

[0048] Example 4

[0049] A lithium-sodium mixed ion battery active material Na 0.8 Li 0.2 Mg 0.4 Fe 0.6 The preparation method of PO4 comprises the following steps:

[0050] (1) using sodium dihydrogen phosphate, iron phosphate, and sodium carbonate as reaction raw materials and using metal magnesium powder as a reducing agent, mixing them in a molar ratio of sodium, magnesium, iron, and phosphorus of 0.8:0.4:0.6:1 to obtain a mixed product;

[0051] (2) ball milling the mixed product obtained in step (1) under nitrogen for 8 hours, sintering the ball milled product under nitrogen at a temperature of 350° C. for 6 hours to obtain a primary sintered product;

[0052] (3) The primary sintered product obtained in step (2) and lithium hydroxide are ball-milled in a sodium to lithium molar ratio of 0.8:0.2, and the ball-milled product is secondary sintered under nitrogen at a secondary sintering temperature of 750° C. The material is kept warm for 4 hours. After cooling, the product is ground to obtain.

[0053] Example 5

[0054] A lithium-sodium mixed ion battery active material Na 0.9 Li 0.1 Ti 0.1 Fe 0.8 The preparation method of PO4 comprises the following steps:

[0055] (1) using sodium dihydrogen phosphate, iron phosphate, and sodium carbonate as reaction raw materials and using metal titanium powder as a reducing agent, mixing them in a molar ratio of sodium, titanium, iron, and phosphorus of 0.9:0.1:0.8:1 to obtain a mixed product;

[0056] (2) ball milling the mixed product obtained in step (1) under nitrogen for 8 hours, sintering the ball milled product under nitrogen at a temperature of 350° C. for 6 hours to obtain a primary sintered product;

[0057] (3) The primary sintered product obtained in step (2) and lithium hydroxide are ball-milled in a sodium to lithium molar ratio of 0.9:0.1, and the ball-milled product is secondary sintered under nitrogen at a secondary sintering temperature of 750° C. The material is kept warm for 4 hours. After cooling, the product is ground to obtain.

[0058] Example 6

[0059] A lithium-sodium mixed ion battery active material Na 0.9 Li 0.1 Zn 0.1 Fe 0.9 The preparation method of PO4 comprises the following steps:

[0060] (1) using sodium dihydrogen phosphate, ferric phosphate, and sodium carbonate as reaction raw materials and metallic zinc powder as a reducing agent, mixing them in a molar ratio of sodium, zinc, iron, and phosphorus of 0.9:0.1:0.9:1 to obtain a mixed product;

[0061] (2) ball milling the mixed product obtained in step (1) under nitrogen for 8 hours, sintering the ball milled product under nitrogen at a temperature of 350° C. for 6 hours to obtain a primary sintered product;

[0062] (3) The primary sintered product obtained in step (2) and lithium hydroxide are ball-milled in a sodium to lithium molar ratio of 0.9:0.1, and the ball-milled product is secondary sintered under nitrogen at a secondary sintering temperature of 750° C. The material is kept warm for 4 hours. After cooling, the product is ground to obtain.

[0063] Example 7

[0064] A lithium-sodium mixed ion battery active material Na 0.8 Li 0.2 Cr 0.2 Fe 0.7 The preparation method of PO4 comprises the following steps:

[0065] (1) using sodium dihydrogen phosphate, iron phosphate, and sodium carbonate as reaction raw materials and metallic chromium powder as a reducing agent, mixing them in a molar ratio of sodium, chromium, iron, and phosphorus of 0.8:0.2:0.7:1 to obtain a mixed product;

[0066] (2) ball milling the mixed product obtained in step (1) under nitrogen for 8 hours, sintering the ball milled product under nitrogen at a temperature of 350° C. for 6 hours to obtain a primary sintered product;

[0067] (3) The primary sintered product obtained in step (2) and lithium hydroxide are ball-milled in a sodium to lithium molar ratio of 0.8:0.2, and the ball-milled product is secondary sintered under nitrogen at a secondary sintering temperature of 750° C. The material is kept warm for 4 hours. After cooling, the product is ground to obtain.

[0068] Comparative Example 1

[0069] A method for preparing a sodium iron phosphate NaFePO4 / C active material comprises the following steps:

[0070] S1, using sodium dihydrogen phosphate, ferric phosphate, and sodium carbonate as reaction raw materials, and glucose as a reducing agent and carbon source to obtain a mixed product;

[0071] S2, ball milling the mixed product obtained in step S1 for 8 hours, placing the ball milled product under nitrogen for a sintering at a temperature of 350° C. and keeping the material warm for 6 hours to obtain a primary sintering product;

[0072] S3. After ball milling the primary sintered product, a secondary sintering is performed under nitrogen. The secondary sintering temperature is 750° C. The material is kept warm for 4 hours. After cooling, the product is ground to obtain.

[0073] Take the sodium ion battery positive electrode material, polyvinylidene fluoride binder and carbon black conductive agent prepared in Examples 1-7 and Comparative Example 1, mix the sodium ion positive electrode material, binder and conductive agent in a mass ratio of 8:1:1, add an appropriate amount of N-methylpyrrolidone to make a viscous slurry, apply it on a rough aluminum foil, bake it in a vacuum drying oven at 80°C for 8 hours, and after it is completely dried, use a punching machine to make the entire electrode into a disc electrode of appropriate size for use. Use metallic sodium as the counter electrode, glass fiber as the diaphragm, 1mol / LNaClO4 (solvent volume ratio of EC and DEC is 1:1) as the electrolyte, and assemble 2016 button cells in an argon protective glove box. The battery was tested in the voltage range of 2.0 to 4.0V, and the results are shown in Table 1:

[0074] Table 1 Electrochemical performance test data of sodium ion batteries

[0075]

[0076] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A method for preparing a lithium-sodium mixed ion battery active material, characterized in that: The following steps are involved: (1) Using a phosphorus source, an iron source, and a sodium source as reaction raw materials and nano-metal as a reducing agent, the mixture is mixed in a set ratio to obtain a mixed product; (2) ball milling the mixed product obtained in step (1) under an inert atmosphere, and sintering the ball milled product under an inert atmosphere to obtain a primary sintered product; (3) ball-milling the primary sintered product obtained in step (2) and the lithium source, and then performing a secondary sintering on the ball-milled product under an inert atmosphere, and grinding the product after cooling to obtain; The chemical formula of the active material of the lithium-sodium mixed ion battery is Na 1-z Li z M x Fe y PO4, 0<x<1, 0<y<1, 0<z≤0.2, M is selected from one or more of Mg, Al, Ti, V, Zn, Cr.

2. The method for preparing the active material for lithium-sodium mixed ion batteries according to claim 1, characterized in that: In step (1), the phosphorus source is one or more of ammonium dihydrogen phosphate, diammonium hydrogen phosphate, sodium dihydrogen phosphate and phosphorus pentoxide.

3. The method for preparing the active material for lithium-sodium mixed ion batteries according to claim 1, characterized in that: In step (1), the iron source is one or more of ferric phosphate and ferric oxide.

4. The method for preparing the active material for lithium-sodium mixed ion batteries according to claim 1, characterized in that: In step (1), the sodium source is one or more of sodium carbonate, sodium bicarbonate, sodium hydroxide, sodium acetate, sodium phosphate, sodium hydrogen phosphate, sodium oxalate, sodium formate, sodium citrate, sodium pyrophosphate and sodium metaphosphate.

5. The method for preparing the active material for lithium-sodium mixed ion batteries according to claim 1, characterized in that: In step (1), the lithium source is one or more of lithium carbonate, lithium hydroxide, lithium dihydrogen phosphate, dilithium hydrogen phosphate, and lithium phosphate.

6. The method for preparing the active material for lithium-sodium mixed ion batteries according to claim 1, characterized in that: In step (2), the mixed product is placed in a planetary ball mill for ball milling under an inert atmosphere, and the ball milling time is 0.5 to 24 hours.

7. The method for preparing active materials for lithium-sodium mixed ion batteries according to claim 1, characterized in that: In step (2), the primary sintering temperature is 300-500°C, and the material insulation time is 4-12 hours.

8. The method for preparing the active material for lithium-sodium mixed ion batteries according to claim 1, characterized in that: In step (3), the primary sintered product and the lithium source are placed in a planetary ball mill for ball milling, and the ball milling time is 0.5 to 12 hours.

9. The method for preparing active materials for lithium-sodium mixed ion batteries according to claim 1, characterized in that: In step (3), the secondary sintering temperature is 600-800°C, and the material insulation time is 2-6 hours.

Citation Information

Patent Citations

  • Carbon-coated iron phosphate sodium-vanadium phosphate sodium composite material and preparation method thereof

    CN105161688A

  • Synthesis method of sodium-ion battery positive electrode material phosphoric acid ferric pyrophosphate sodium / carbon and sodium-ion battery prepared from sodium-ion battery positive electrode material phosphoric acid ferric pyrophosphate sodium / carbon

    CN115148976A

  • Preparation method for electrochemical active material

    CN102569802A

  • Synthesis method of positive electrode material sodium ferric phosphate for sodium ion battery

    CN114759179A

  • Lithium-sodium-potassium mixed type positive electrode active material as well as preparation method and application thereof

    CN116190641A